2014
DOI: 10.1186/1476-4598-13-261
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-610 promotes proliferation and tumorigenicity and activates Wnt/β-catenin signaling in human hepatocellular carcinoma

Abstract: BackgroundWnt/β-catenin signaling pathway plays important roles in human cancer progression. Better understanding the mechanism underlying regulation of Wnt/β-catenin signaling pathway might provide novel therapeutic targets for cancer treatment.MethodsmiR-610 expression levels in hepatocellular carcinoma (HCC) cell lines, HCC tissues and 76 archived HCC specimens were determined using real-time PCR. Cell viability was measured by 3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…We and others have provided data to support the involvement of small ncRNAs, such as microRNAs, in the modulation of liver cell proliferation and apoptosis 10–13. Despite several studies linking ncRNA and the Wnt pathway, most of them focused on the modulation of Wnt signalling proteins by microRNAs, little is known about the effect of this pathway on ncRNA 14–17. Increasing evidence points to an important regulatory role of long ncRNAs in cellular processes and disease phenotypes.…”
Section: Introductionmentioning
confidence: 97%
“…We and others have provided data to support the involvement of small ncRNAs, such as microRNAs, in the modulation of liver cell proliferation and apoptosis 10–13. Despite several studies linking ncRNA and the Wnt pathway, most of them focused on the modulation of Wnt signalling proteins by microRNAs, little is known about the effect of this pathway on ncRNA 14–17. Increasing evidence points to an important regulatory role of long ncRNAs in cellular processes and disease phenotypes.…”
Section: Introductionmentioning
confidence: 97%
“…6). LRP6 has been shown to function as an oncogene by promoting cell growth, invasion and migration, and is expected to be a target for cancer therapy (40)(41)(42)(43)(44)(45). Notably, there is evidence that ERK1/2 in the RAS/MAPK pathway could facilitate WNT/β-catenin signaling via LRP6 phosphorylation on serine-1490 (S1490) and threonine-1572 (T1572) at both mature (transmenbrane LRP6) and immature state during its Golgi network-based maturation process (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…TBL1X is a potential target of miR-138-5p, as predicted by the IPA's microRNA Target Filter tool. TBL1X functions as an oncogene in the proliferation and tumorigenesis of hepatocellular carcinoma (HCC) cells through activating WNT/β-catenin signaling [47]. The bioinformatics approaches in our study revealed that the miRNA signature identified gene targets involved in the WNT/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 93%